2009
DOI: 10.1038/jid.2008.323
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 Is the Constitutive Functional Sheddase of CD44 in Human Melanoma Cells

Abstract: CD44 proteins are cell surface receptors for hyaluronic acid (HA), a component of the extracellular matrix that has multiple effects on cell behavior. CD44 can be shed from the cell surface by proteolytic cleavage. The resulting soluble form can interfere with the interaction between HA and membrane-bound CD44. Soluble CD44 can abolish the cell proliferation-promoting effect of HA on melanoma cell lines, suggesting that a better understanding of the shedding process might identify ways of blocking tumor cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 48 publications
1
72
0
2
Order By: Relevance
“…Thus, ADAM10, not ADAM17, plays an essential role in the shedding of MICA in human HCC cells. Anderegg and colleagues (23) reported that only ADAM10, not ADAM17, contributed to shedding of CD44 molecules in human melanoma cells although both ADAM10 and ADAM17 proteases were significantly expressed in human melanoma tissues, suggesting that ADAM10 and ADAM17 do not always work in a similar manner. A recent report showed that ADAM10, but not ADAM17, could directly bind to calmodulin (24), which may involve the difference of MICA cleavage between ADAM10 and ADAM17 proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ADAM10, not ADAM17, plays an essential role in the shedding of MICA in human HCC cells. Anderegg and colleagues (23) reported that only ADAM10, not ADAM17, contributed to shedding of CD44 molecules in human melanoma cells although both ADAM10 and ADAM17 proteases were significantly expressed in human melanoma tissues, suggesting that ADAM10 and ADAM17 do not always work in a similar manner. A recent report showed that ADAM10, but not ADAM17, could directly bind to calmodulin (24), which may involve the difference of MICA cleavage between ADAM10 and ADAM17 proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Pan et al (32) found that in the pituitary adenoma cell line, AtT-20, ADAM10 facilitated cell migration through modulation of CD44 and L1 cleavage. In another study, Anderegg et al (33) showed that ADAM10 is the predominant protease involved in the constitutive shedding of endogenous CD44 from melanoma cells. Multiple cell signaling pathways are responsible for cellular proliferation and migration (34).…”
Section: Discussionmentioning
confidence: 99%
“…4). It has been demonstrated that cleavage of CD44 by MMP-14 is a prerequisite for MMP-14-enhanced cell migration (9,33,42,43), although MMP-14 is reported to be unnecessary for CD44-shedding in melanoma cells (44). Using a functional assay, we observed that coexpression of MMP-14 but not catalytic inactive MMP-14 mutant (E 240 3 A) in COS-1 cells significantly reduced cell adhesion ability to hyaluronic acid (a CD44 ligand)-coated culture plates (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%